2000
DOI: 10.1093/ajcn/71.4.962
|View full text |Cite
|
Sign up to set email alerts
|

Plasma total homocysteine, pregnancy complications, and adverse pregnancy outcomes: the Hordaland Homocysteine Study

Abstract: Elevated tHcy concentration is associated with common pregnancy complications and adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
3
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(195 citation statements)
references
References 37 publications
15
167
3
10
Order By: Relevance
“…Homocysteine is metabolized with folate as a cosubstrate and vitamin B 12 as a cofactor, and low levels of these vitamins cause hyperhomocysteinemia [43]. Elevated homocysteine concentration is associated with common pregnancy complications and adverse pregnancy outcomes [44]. Dodds et al [45] have shown that increased homocysteine is associated with pregnancy loss, gestational hypertension, preeclampsia and small gestational age infants.…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is metabolized with folate as a cosubstrate and vitamin B 12 as a cofactor, and low levels of these vitamins cause hyperhomocysteinemia [43]. Elevated homocysteine concentration is associated with common pregnancy complications and adverse pregnancy outcomes [44]. Dodds et al [45] have shown that increased homocysteine is associated with pregnancy loss, gestational hypertension, preeclampsia and small gestational age infants.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the data on folate deficiencies are based on small, local surveys, but they suggest that folate deficiency may be a public health problem affecting millions of people globally [18]. Folate and vitamin B 12 deficiencies are associated with adverse pregnancy outcomes including LBW and preterm birth [20]. A substantial proportion of neural tube defects are related to inadequate consumption of folic acid around the time of conception and in some populations associated with genetic factors that increase the need for dietary folic acid.…”
Section: Maternal Micronutrient Deficiency: Burden Significance and mentioning
confidence: 99%
“…A study in India showed that women with higher autonomy (defined as a woman's personal power in the household and her ability to influence and change her environment) were significantly less likely to have a stunted child than their peers who had less autonomy [80]. An analysis of survey data from 17 developing countries confirms a positive association between maternal education and nutritional status in children 3-23 months of age [20]. Poverty and food security conditions in a geographical location have a significant impact on maternal and child undernutrition [81].…”
Section: Way Forwardmentioning
confidence: 99%
“…Folate status is the major determinant of plasma homocysteine level, and there is a strong inverse correlation between plasma homocysteine level and serum or erythrocyte folate levels [17]. Folate and B12 deficiencies have been found to be associated with adverse pregnancy outcomes including both LBW and preterm birth [18]. …”
Section: Undernutrition Epidemiologymentioning
confidence: 99%